Conjugative transmission of antibiotic-resistance from stream water Escherichia coli as related to number of sulfamethoxazole but not class 1 and 2 integrase genes. (1st November 2016) - Suhartono, Suhartono; Savin, Mary
ABSTRACT: A conjugation assay was used to determine the effects of phenotypic resistance to one to up to 5 antibiotics, sampling site of origin, presence or absence of class 1 and/or class 2 integrase ( intI ) genes ( intI1 and intI2 ), and the number of sulfamethoxazole resistance ( sul ) and trimethoprim resistance ( dfr ) genes on the transfer frequencies of plasmids from environmental, antibiotic-resistant Escherichia coli . Of 51 sulfamethoxazole and trimethoprim-resistant E. coli isolates conferring at least one mob gene ( mob P51, mob F11, mob F12, mob Q11, mob Q12, or mob Qu ), 38 produced transconjugants with an overall mean frequency of 1.60 × 10 −3 transconjugants/ donors (T/D) or 5.89 × 10 −3 transconjugants/recipients (T/R). The presence or absence of intI1 and intI2 and the presence or absence of different targeted dfr genes ( dfrA1, dfrA8, dfrA12, dfrA14, dfrA17, and/or dfrB3 ) were not statistically related to plasmid transfer frequencies as determined by ANOVA ( P ≥ 0.05). However, E. coli isolates recovered 2 km downstream of wastewater treatment plant effluent input, and those possessing resistance to 3 antibiotics had significantly greater plasmid transfer frequency than their counterparts when calculated as T/D (ANOVA followed by Fisher's least significant difference means comparison, P < 0.05). Greater plasmid transfer frequency calculated as T/D was also measured for E. coli possessing 3 compared to a single sul gene. The in-vitro frequency suggests that horizontal gene transfer of conjugative mediated-antibiotic ( sul ) resistance genes may be significant among resistant, stream bacteria.